Respuesta :
Answer:
4√7*a^3
Step-by-step explanation:
a^6 is the same as (a^3)^2. If we take the square root of this latter expression, the result will be a^3.
112 can be factored as follows: 2 * 56
2 * 7 * 8
2 * 7 * 2 * 4, or 7 4^2
Taking the square root of this last result yields 4√7.
Thus, √ (112a^6) = 4√7*a^3
The simplified form of the expression is [tex]4a^3\sqrt{7}[/tex]
Given the indices, [tex]\sqrt{ 112a^6}[/tex], we need to remove all the perfect squares from the square root. This is as shown below:
Applying the law of indices, the expression will become:
[tex]\sqrt{ 112a^6} \\=\sqrt{16 \times 7 \times (a^3)^2}\\=4\sqrt{7} \times \sqrt{(a^3)^2}\\= =4\sqrt{7} \times a^3\\=4a^3\sqrt{7}[/tex]
Hence the simplified form of the expression is [tex]4a^3\sqrt{7}[/tex]
Learn more here: https://brainly.com/question/20298728